Examining the influences of experience, personality and attitude on SCUBA divers’ underwater behaviour: a structural equation model - Ong, T.F.; Musa, G. (Elsevier, 2014)
This study examines and extends the empirical evidence of the causal relationships among experience, personality and attitude on the behaviour of scuba divers. The empirical data were collected from divers (n = 413) in the five most popular islands for scuba diving in Malaysia. Measurements of diving attitude, experience and underwater behaviour were developed based on the literature and expert opinions. The ‘Big Five’ model was utilised to measure the personality of divers. Data were analysed using the structural equation modelling to examine the relationships among the constructs. Past experience was found to be the most important factor in explaining divers’ underwater behaviour, followed by diving attitude and personality. Diving attitude partially mediates the relationships between experience and underwater behaviour. The paper discusses some of its theoretical and managerial ontributions which could facilitate the design and management of potential detrimental impacts caused by divers in the marine environment.